Entrepreneurial intention challenge in TVET education - Abu Bakar, Kamarudin; Ismail, Albert Feisal @ Muhd Feisal; Mohamad, Mohd Amin; Ahmat, Norun Najjah; Sahlan, Mohd Khairulnizam; Muhammad Khodri Harahap, Afif Zuhri (Penerbit UTHM, 2024)
Effective entrepreneurship course among TVET students are critical. The economic situation can be revived by new business venture. Knowledge learnt promotes self-reliance while real practices made meaningful contributions to the nation. 108 respondents were selected through convenience sampling from 2 engineering programs at a public TVET university in Melaka. Descriptive analysis yields high mean values between 81.5%-91.7% on perceive importance, business interest, sales/marketing skills, enjoy practical activities, and understand syllabus where 19.4% of the students managed to own legitimate business. The study used hybrid analysis between SPSS on the moderating effect and SEM-AMOS on the mediating effect. In the first analysis, the study examined whether “course delivery” could induce a moderating effect on the model understudy. The 3 variables correlated well with one another. Multiple regression showed significant “entrepreneurial intention” among students. Although “course delivery” explains further 2.5% variance in the “appropriate behaviors”, the model interaction has a negative effect toward students’ “entrepreneurial intention”. In second analysis, AMOS was used as CFA to test and validate the mediating effect on the variables direct, indirect and total effects dimensions. The outputs demonstrate acceptable goodness of fit indices from the measurement model where Chi-square and comparative fit (CMin/df, CFI, SRMR, and RMSEA) values were statistically significant at 0.5 level. However, the value of 0.072 at the variables intersection concludes that “course delivery” did not mediate the relationship between “appropriate behaviors” and “entrepreneurial intention”. Hence, both analysis results were consistent in which “course delivery” was not the main factor in determining an effective “entrepreneurial intention” among the TVET engineering students. It suggested the improve of “appropriate behaviors” factors assimilation to become global entrepreneurs and self-sustained TVET graduates.